2016
DOI: 10.1002/ps.4246
|View full text |Cite
|
Sign up to set email alerts
|

Allelobiosis in the interference of allelopathic wheat with weeds

Abstract: Through root-secreted chemical signals, allelopathic wheat can detect competing weeds and respond by increased allelochemical levels to inhibit them, providing an advantage for its own growth. Allelopathy and allelobiosis are two probably inseparable processes that occur together in wheat-weed chemical interactions. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 43 publications
6
50
0
1
Order By: Relevance
“…Furthermore, roots may be capable of detecting neighboring roots and responding them by root‐secreted allelochemicals and non‐toxic signals . Several studies have shown that root‐secreted non‐toxic signals can participate in root–root recognition and interactions . Data generated in this study showed that increased barnyardgrass inhibition and rice allelochemicals occurred under root segregation with nylon mesh.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, roots may be capable of detecting neighboring roots and responding them by root‐secreted allelochemicals and non‐toxic signals . Several studies have shown that root‐secreted non‐toxic signals can participate in root–root recognition and interactions . Data generated in this study showed that increased barnyardgrass inhibition and rice allelochemicals occurred under root segregation with nylon mesh.…”
Section: Discussionmentioning
confidence: 64%
“…28,29 Several studies have shown that root-secreted non-toxic signals can participate in root-root recognition and interactions. 30,40 Data generated in this study showed that increased barnyardgrass inhibition and rice allelochemicals occurred under root segregation with nylon mesh. Furthermore, the production of rice allelochemicals was induced by the root exudates of barnyardgrass, regardless of biotypes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…; Li et al . ). Data generated in this study showed that increased weed inhibition and rice allelochemical production occurred under root segregation with nylon mesh.…”
Section: Discussionmentioning
confidence: 97%
“…Muitas culturas tem o potencial de produzir, liberar e exsudar diferentes aleloquímicos para a rizosfera e atmosfera, e inibem o crescimento de plantas daninhas e de outras culturas nas suas imediações (Shah et al, 2016). Por exemplo, a inibição do crescimento de plantas daninhas quando em competição com o trigo, através da liberação de compostos alelopáticos pelas raízes da cultura (Li et al, 2016).…”
Section: Alterações No Metabolismo Secundário Decorrentes Da Interferunclassified